2005
DOI: 10.1097/01.aids.0000161772.51900.eb
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a brief case management intervention to link recently diagnosed HIV-infected persons to care

Abstract: A brief intervention by a case manager was associated with a significantly higher rate of successful linkage to HIV care. Brief case management is an affordable and effective resource that can be offered to HIV-infected clients soon after their HIV diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
343
5
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(363 citation statements)
references
References 13 publications
8
343
5
2
Order By: Relevance
“…Respondents in our study appear to have had one or fewer encounters with a case manager, which may not be optimal. Previous studies had shown that for newly diagnosed HIV-infected persons, linkage to care activities are more successful when persons have an average of two or more encounters with a case manager (Craw et al, 2008;Gardner et al, 2005). These data support previous findings describing the benefit of ongoing linkage to care activities that may include multiple follow-up encounters to increase the chances of successful linkage to care.…”
Section: Perception Of Follow-up Servicessupporting
confidence: 86%
See 1 more Smart Citation
“…Respondents in our study appear to have had one or fewer encounters with a case manager, which may not be optimal. Previous studies had shown that for newly diagnosed HIV-infected persons, linkage to care activities are more successful when persons have an average of two or more encounters with a case manager (Craw et al, 2008;Gardner et al, 2005). These data support previous findings describing the benefit of ongoing linkage to care activities that may include multiple follow-up encounters to increase the chances of successful linkage to care.…”
Section: Perception Of Follow-up Servicessupporting
confidence: 86%
“…Respondents agreed that passive referrals were of little help and provided minimal, if any, assistance in accessing care. As shown in previous studies, active referrals are more successful for linking newly diagnosed persons to care (Craw et al, 2008, Gardner et al, 2005. The addition of a detailed, standard definition of an active referral in future CTR guidelines may be necessary to support the provision of an optimal level of service when referring to or providing linkage to care services.…”
Section: Perception Of Follow-up Servicesmentioning
confidence: 84%
“…Los principales obstáculos para lograr un resultado óptimo del tratamiento en personas con HIV/ sida, son el diagnóstico tardío, la demora en la vinculación a los centros de atención, la deficiente retención de los pacientes en dichos centros, la demora en el inicio del tratamiento antirretroviral y su incumplimiento (descontinuación o intermitencia del tratamiento), así como la ausencia de tratamiento para las enfermedades concomitantes no asociadas al HIV y las necesidades básicas insatisfechas (42)(43)(44).…”
Section: Discussionunclassified
“…HIV case management is associated with increased utilization of support services and a decrease in unmet needs [22,23]. A brief, focused case management system in U.S. urban centers helped newly diagnosed HIV-positive individuals successfully access HIV care [24]. Among HIVinfected homeless and marginally-housed individuals, case management was associated with improved self-reported antiretroviral adherence and increased CD4 cell count [25].…”
Section: Introductionmentioning
confidence: 99%